Síntese de N-Alquilsulfonamidas análogas do PABA com potencial atividade antagonista de canais iônicos - Martins, Carina Couto [UNESP] (2015)
The development of new drugs more efficient, less toxic and with fewer side effects has been a subject of great importance and scientific interest. Un this context the present work shows the sythesis of new sulfonated compounds analogues of PABA, with potential interesting pharmacological properties, as the effect or blocking activity on ion channels of voltage gated potassium. In addition, some of these sufonamides, have N-(aminoalkyl) lactams as side chain. These lactamic groups have been described as inhibitors of human tryptase, an important mediator in asthma, and activity as HIV-1 protease inhibitors. The physical-chemical analyses have been carried out by different spectrocopic (1H and 13C NMR, FT-IR) and spectrometric techniques (EI-MS and ESI-MS). The structures of all compounds were unambiguously confirmed. A study for High Resolution Mass Spectrometry was peformed for all products. This study allowed to observe the formation of sulfoxylates ions and to propouse mechanisms to explain this and other experimental fragments. The synthesized molecules are under current investigation of its inhibiting channels and some molecules showed good results